Specifying Standard and Criteria Levels of Administrative Work Performance and Artistic Activities Scale For Iraq Sport Teams - Aziz, Nashaat; Hamad, Thamer (Journal of Physical Education, 2019)
The problem of the research lies in identifying sport clubs’ work and its annual value to provide the proper financial support required for this work. The research aimed at identifying the standard and criteria levels of administrative work and artistic activities’ scale for Iraqi sport clubs. The researchers used the descriptive method on (450) member of Iraqi sport clubs. The data was collected and treated using proper statistical operations to conclude a standardized scale for evaluating administrative work and artistic activities for Iraqi sport clubs as well as differentiating between different levels. Finally the researchers concluded applying this scale on sport clubs as a reference for continuous improvement. In addition to that, stressing team creativity through interaction among administrative board members.